Implementation of the Read, Observe, Auditory, Review (ROAR) Learning Model as an Effort to Improve Cognitive Learning Outcomes of Grade IV Social Studies Students at SD - Mely Tri Mulidya; Didit Yulian Kasdriyanto; Ryzca Siti Qomariyah (JURNAL PENDIDIKAN IPS, 2025)
Using natural disaster-related content for fourth-grade students at SDN Klenang Lor 1, this research attempts to enhance students' cognitive learning outcomes using the Read, Observe, Auditory, Review (ROAR) learning paradigm. Planning (plan), action (act), observation (observe), and reflection (reflect) are the four steps of the Kemmis & McTaggart classroom action research (CAR) technique, which was used to conduct the study. 24 individuals, 16 of whom were male and 8 of whom were female, were the participants of this research. They were all fourth grade pupils at SDN Klenang Lor 1. There were two cycles in this research, with one meeting each cycle. Learning outcomes increased from 54.16% in cycle I to 87.5% in cycle II, according to the study's findings.